Popularity of Coaching “Classes” In India - Bharucha, Jehangir (International Business Education Journal, 2016)
Coaching classes have gained immense popularity in the metropolitan cities of India in recent times. There are classes catering to diverse needs in terms of different courses, varying timings and locations and course material requirements. The main purpose of this research paper is to identify how popular coaching classes are with the students pursuing commerce based courses in the city of Mumbai. With the help of a structured questionnaire circulated among a sample of students from Mumbai University, the paper aims at identifying the need and relevance of coaching classes and tries to understand the gaps in the education system. The study concludes that the need for coaching classes has much to do with disillusionment with college faculty and to a large extent to supplement the learning done at college. The paper recommends policy measures in this regard.